1992
DOI: 10.1002/cjce.5450700512
|View full text |Cite
|
Sign up to set email alerts
|

The internally circulating fluidized bed (ICFB): A novel solution to gas bypassing in spouted beds

Abstract: The bypassing of a portion of the inlet spout gas to the annular region of spouted and spout‐fluid beds can have a critical effect on processes requiring accurate control of the spout gas residence time even when a draft tube is utilized. A modification to the spout‐fluid bed with draft tube called the Internally Circulating Fluidized Bed or ICFB is proposed which eliminates this bypassing problem. Experiments were conducted on a cold 20 cm diameter semi‐cylindrical unit to define the operational characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 10 publications
(4 reference statements)
1
37
0
Order By: Relevance
“…Stocker et al [20] observed the occurrence of gas bypassing or backflow in spouted and spout fluid beds with draft tubes. Milne et al [21] reported to have eliminated bypassing of gas totally using a draft tube (or riser) fixed directly to the inlet gas nozzle and providing a number of orifices on the wall of the tube near its base. Yang and Keairns [5] carried out modifications in design and operating parameters in a draft tube system and succeeded in reducing the gas bypass.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Stocker et al [20] observed the occurrence of gas bypassing or backflow in spouted and spout fluid beds with draft tubes. Milne et al [21] reported to have eliminated bypassing of gas totally using a draft tube (or riser) fixed directly to the inlet gas nozzle and providing a number of orifices on the wall of the tube near its base. Yang and Keairns [5] carried out modifications in design and operating parameters in a draft tube system and succeeded in reducing the gas bypass.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Ijichi et al (1998) reviewed the flow characteristics of a spouted bed with a draft tube. The applications of spouted bed with a draft tube include coal combustion (Konduri et al, 1995), pneumatic conveying (Milne et al, 1992), pyrolysis of hydrocarbon (Stocker et al, 1989) and particle circulation (Ji et al, 1998). Kalwar and Raghavan (1992) investigated the spout pressure drop and minimum spouting superficial velocity in a two-dimensional gas-spouted bed.…”
Section: Introductionmentioning
confidence: 99%
“…Milne et al [25] showed that C d depended on the particle size, and Ahn et al [20] revealed that C d was a function of the orifice size d or and particle size …”
Section: Correlationsmentioning
confidence: 98%